The Lived Experiences of Self-Care to Prevent Infection among Patients with Leukemia Undergoing Chemotherapy During COVID - 19 Pandemic: Samonnan Thasaneesuwan - Punsuk, Chaweewan; Thasaneesuwan, Samonnan; Nilmanat, Kittikorn (Princess of Naradhiwas University Journal, 2024)
Descriptive phenomenological qualitative research was employed to explore the lived experiences of self-care to prevent infection among patients with leukemia undergoing chemotherapy during COVID-19 pandemic. Twelve participants, all of whom were leukemia undergoing chemotherapy during COVID-19 pandemic, were included in the study by purposing sampling. Data were collected through in-depth individual interviews and analyzed using the Colaizzi method. The study revealed two main themes encapsulating the lived experiences of self-care to prevent infection among patients with leukemia undergoing chemotherapy during COVID-19 pandemic: 1) new normal ways for self-care, and 2) boosting psychological immunity. The findings contribute to a deeper understanding of the lived experiences involved in self-care to prevent infection among leukemia patients undergoing chemotherapy during COVID - 19 pandemic. Furthermore, the insights gained from this study can inform the development of nursing intervention aimed at providing support for self-care to prevent infection among patients with leukemia during the COVID-19 pandemic or other infectious and communicable disease.